Honesty Speaks a Second Language. (1st July 2018) - Bereby‐Meyer, Yoella; Hayakawa, Sayuri; Shalvi, Shaul; Corey, Joanna D.; Costa, Albert; Keysar, Boaz
Abstract: Theories of dishonest behavior implicitly assume language independence. Here, we investigated this assumption by comparing lying by people using a foreign language versus their native tongue. Participants rolled a die and were paid according to the outcome they reported. Because the outcome was private, they could lie to inflate their profit without risk of repercussions. Participants performed the task either in their native language or in a foreign language. With native speakers of Hebrew, Korean, Spanish, and English, we discovered that, on average, people inflate their earnings less when they use a foreign language. The outcome is explained by a dual system account that suggests that self‐serving dishonesty is an automatic tendency, which is supported by a fast and intuitive system. Because using a foreign language is less intuitive and automatic, it might engage more deliberation and reduce the temptation to lie. These findings challenge theories of ethical behavior to account for the role of the language in shaping ethical behavior. Abstract : Bereby‐Meyer, Hayakawa, Shalvi, Corey, Costa and Keysar investigate lying for self‐serving reasons. Participants in their experiments had to report the outcome of rolling a die only known to them. They inflated their outcomes less, and thus lied less, when using a foreign language than when using their native language. The authors suggest that lying for self‐serving reasons is an automatic tendency that can be overcome by speaking in a foreign language. [71]